Validação da versão brasileira do World Health Organization Disability Assessment Schedule (WHODAS 2.0) em mulheres com dor pélvica crônica - Brito, Gleiciane Aguiar (2023)
Introduction: Chronic pelvic pain (CPP) is a persistent pain perceived in structures related to the pelvis for at least 6 months. It is pain is often associated with negative cognitive, behavioral, sexual and emotional consequences. There are currently no validated tools in the Brazilian literature for measuring functioning according to the biopsychosocial model presented by International Classification of Functioning, Disability and Health (ICF) for patients with CPP. However, the World Health Organization Disability Assessment Schedule (WHODAS 2.0) is an instrument created specifically for measuring functioning and disability. Objective: To test the measurement properties of the WHODAS 2.0 for women with CPP based on the analysis of its reliability, construct validity and discriminative validity. Method: It is a validation study, was carried out from April 2019 to november 2021 at the CPP, Endometriosis and Pelvic Physiotherapy outpatient clinic at the Assis Chateaubriand Maternity (Fortaleza–Ceará–Brazil). Women, aged 18 years or older, with a clinical diagnosis of CPP were included. The questionnaires were applied through two interviews, the first being face-to-face and the second via telephone between 7 and 14 days after the first application. The following auxiliary instruments were used in the validation process of the WHODAS 2.0 instrument: The Quality of Life Questionnaire (SF-12), the Visual Numerical Pain Scale, in addition to an evaluation form with sociodemographic and clinical data. Internal consistency was analyzed using Cronbach’s alpha coefficient, construct validity was assessed using Spearman’s correlation coefficient, discriminative validity was analyzed using the analysis of variance (Anova), test-retest reliability was analyzed using the Intra-class Correlation Coefficient (ICC). Results: The data of 128 women with a mean age of 34.97 (±8.0) years were included. The results obtained indicate that the WHODAS 2.0 presented good psychometric properties in the studied population. Reliability analyzes showed satisfactory results in terms of internal consistency (Cronbach’s alpha = 0,71 to 0,94) and excellent results in test-retest reliability (IIC= 0.69 – 0.91). Validity analyzes showed a strong to moderate correlation in construct validity between the total WHODAS score and the physical (rho=0,7, p<0,001) and mental components of the SF-12 (rho=0,67, p<0,0001), and statistically significant values for discriminative validity according to pain intensity in the last 30 days (p < 0,001). Conclusion: The Brazilian version of the WHODAS 2.0 with 36 items instrument proved to be a reliable and valid questionnaire for investigating the functioning of the Brazilian women with CPP.